A Prospective Longitudinal Quality Initiative toward Improved Enhanced Recovery after Cesarean Pathways - Cojocaru, Liviu; Alton, Suzanne; Pahlavan, Autusa; Coghlan, Martha; Seung, Hyunuk; Trilling, Ariel; Kodali, Bhavani S.; Crimmins, Sarah; Goetzinger, Katherine R. (American Journal of Perinatology, 2023)
Objective This study aimed to evaluate whether enhanced recovery after cesarean (ERAC) pathways reduces inpatient and outpatient opioid use, pain scores and improves the indicators of postoperative recovery.Study Design This is a prospective, longitudinal, quality improvement study of all patients older than 18 undergoing an uncomplicated cesarean delivery (CD) at an academic medical center. We excluded complicated CD, patients with chronic pain disorders, chronic opioid use, acute postpartum depression, or mothers whose neonate demised before their discharge. Lastly, we excluded non-English- and non-Spanish-speaking patients. Our study compared patient outcomes before (pre-ERAC) and after (post-ERAC) implementation of ERAC pathways. Primary outcomes were inpatient morphine milligram equivalent (MME) use and the patient's delta pain scores. Secondary outcomes were outpatient MME prescriptions and indicators of postoperative recovery (time to feeding, ambulation, and hospital discharge).Results Of 308 patients undergoing CD from October 2019 to September 2020, 196 were enrolled in the pre-ERAC cohort and 112 in the post-ERAC cohort. Patients in the pre-ERAC cohort were more likely to require opioids in the postoperative period compared with the post-ERAC cohort (81.6 vs. 64.3%, p < 0.001). Likewise, there was a higher use of MME per stay in the pre-ERAC cohort (30 [20–49] vs. 16.8 MME [11.2–33.9], p < 0.001). There was also a higher number of patients who required prescribed opioids at the time of discharge (98 vs. 86.6%, p < 0.001) as well as in the amount of MMEs prescribed (150 [150–225] vs. 150 MME [112–150], p < 0.001; different shape of distribution). Furthermore, the patients in the pre-ERAC cohort had higher delta pain scores (3.3 [2.3–4.7] vs. 2.2 [1.3–3.7], p < 0.001).Conclusion Our study has illustrated that our ERAC pathways were associated with reduced inpatient opioid use, outpatient opioid use, patient-reported pain scores, and improved indicators of postoperative recovery.Key Points
Keywords: cesarean section; obstetrics; quality of care; maternal health; enhanced recovery after surgery